Prototype Vaccine Candidate of Mycoplasma Pneumoniae - Shnawa, Ibrahim Mohamed Saeed (Vaccines and Vaccine Interference, 2023)
Live, live attenuated, inactivated, bacteriocin, autogenous, subunit and DNA vaccine technologies have been attempted to; evaluate, develop and produce human and animal pathogenic mycoplasma. As concerned with the Mycoplamsa pneumoniae the human specific pathogen the tried prototype vaccine candidates were the; inactivated, attenuated and the subunit molecular vaccine versions. The status of Mycoplasma pneumoniae vaccine still be in the initial active development phases and currently be in laboratory development phase as an experimental vaccine candidate. Though, the old new vaccine version the inactivated pass to very limited human trial. The recent membrane lipoprotein vaccine candidate may be of inferior importance due to the occurrence of vaccine enhancement of disease in mice model.